PENYULUHAN PEMBUATAN NIB KEPADA ANGGOTA POKLAHSAR DI DESA DERMASANDI KABUPATEN TEGAL - Yusuf Wijanarko; Dwi Retno Mudiasih; Isnan Yudi Kurniawan; Ayu Septi Wulandari (Universitas Mataram, 2022)
Dermasandi Village is one of the centers for processing pindang and grilled fish in Pangkah District, Tegal Regency, Central Java Province. The business of processing pindang and grilled fish has been carried out for generations with traditional technology before the independence of the Republic of Indonesia. There are eight groups of fish processors and marketers in Dermasandi Village, namely Poklahsar kuda Laut, Poklahsar Ulam Sari, Poklahsar Sumber Rejeki, Poklahsar Mina Sari, Poklahsar Mina Sejahtera, Poklahsar Sumber Laut, Poklahsar Dermasandi Mina Abadi, Poklahsar Mina Baruna Dermasandi. This community service activity aims to provide additional knowledge of the main actors in fisheries and provide assistance in making NIB for fish processors. The method of activity carried out is providing counseling on Government Regulation No. 5 of 2021 concerning the Implementation of Risk-based Business Licensing, by making NIB (Business Identification Number) through the Risk-Based Online Single Submission (OSS RBA) and practices and demonstrations on how to make NIB. After conducting counseling and demonstrations on how to make NIB during July and August at eight poklahsars, they were able to increase knowledge about the benefits and functions of the legality of licensing in pindang and grilled fish processing businesses. Most of the KBLI for the fishery processing sub-sector are included in KBLI 10212 for smoking/roasting fish industry, KBLI 10214 for the fish processing industry in the category of micro/small business with a low medium risk level and KBLI 47215 for retail trade of fishery products with a low risk classification. The assistance provided by fishery instructors to fish processors through groups of fish processors and marketers can be issued 66 NIB (Enterprise Number) documents through the website https://oss.go.id. Through this assistance in making the NIB document, the main actors and business actors in fisheries processing are helped by obtaining the legality of their business.